Karakterisasi Isolat Bakteri Penghasil Kitinase Dan Glukanase Serta Uji Efektifitasnya Terhadap Jamur Colletotrichum sp - suryadi, yadi -; susilowati, Dwi N; Samudra, I Made - (Universitas Muhammadiyah Surakarta, 2021)
Shallots as a horticultural commodity is quite important in Indonesia. Fungi anthracnose disease caused by fungus Colletotrichum sp. is one of the pathogens causing rot on shallot plants. Therefore, an alternative control that is environmentally friendly is a necessity. The aim of the study was to screen the best potential isolates producing chitinase and glucanase of shallot- rhizosphere from Brebes, and further used to inhibit fungal pathogens. The results showed that it was obtained 8 isolates have suppression activity against Colletotrichum sp. which varied in their inhibition. The highest inhibition was produced by isolate UBS 3 (30.56%), whilst one isolate (TK 3) did not have the ability to inhibit Colletotrichum sp.